Chemical-physical features of the biochar-based oil-destructive sorbent - A. V. Khokhlov (Хімія, фізика та технологія поверхні)
The main task and relevance of this work are to develop the most effective sorbents for cleaning oil pollution or accidental oil spills. A generalized criterion for evaluating the effectiveness of a sorbent is the local availability and fast renewability of raw materials for biochar.